Costos de transacción generados en el proceso presupuestario en el Perú - Alvarado Pérez, Betty M. (2008)
This article presents some of the results obtained from the analysis performed to the health sector budget. The study focused the analysis in the city of Lima. The methodology not only looks for a discussion of resource allocation in the health sector, it goes further and makes an analysis applying a Public Expenditure Tracking Survey (PETS) methodology. The core objective is to discover institutional bottlenecks which make the health expenditures less effective. The novelty in this type of research is the construction of three main flows, which represent the budget execution process; these flows are related to the transfer process of money, goods and services, and salaries; besides these three flows there is an additional one related to information. The topics of analysis are multiple; this article prioritized aspects such as the management of own collected resources from tariffs, goods management (specifically pharmaceuticals), and finally the management of petty cash and budget transfers received by health facilities The study concludes that a poor budget management causes costs to the health system, which sometimes are absorbed by the population and sometimes bythe same health staff. The latter is the origin of perverse incentive to the same personnel who even prefer the status quo. The latter allows them to receive part in their salary from tariffs (with bonus), rather than acquiring needed goods for their facility.